Comparison of perfusion values after percutaneous transluminal angioplasty according to the severity of ischaemia in the diabetic foot. Issue 1 (12th October 2018) - Namgoong, Sik; Yang, Jong‐Phil; Yoo, Ki‐Hyun; Han, Seung‐Kyu; Rha, Seung‐Woon; Lee, Ye‐Na
Abstract : Percutaneous transluminal angioplasty (PTA) is now more frequently used to improve tissue perfusion in ischemic diabetic feet. However, there are concerns about its feasibility and effectiveness in severely ischaemic feet. This study aimed to compare the perfusion values after PTA according to the ischaemic degree of diabetic feet. This study included 133 ischaemic diabetic feet. The foot transcutaneous oxygen pressure (TcPO2 ) and toe pressure were measured before the procedure and every second postoperative week for 6 weeks. The patients were divided into three groups according to ischaemic severity on the basis of TcPO2 and toe pressures. In the "severely ischaemic" group, the TcPO2 increased from 7.5 ± 4.9 to 40.3 ± 11.3 mm Hg (5.4‐fold) 6 weeks after the PTA ( P  < 0.001). The toe pressure increased from 8.5 ± 8.8 to 42.2 ± 19.3 mm Hg (5.0‐fold, P  < 0.001). In the "mild" group, the TcPO2 increased from 35.4 ± 2.5 to 41.8 ± 12.4 mm Hg (1.2‐fold, P  = 0.003), and the toe pressure increased from 45.7 ± 12.3 to 54.3 ± 31.3 mm Hg (1.2‐fold, P  > 0.05). Results of the "intermediate" group were in between. The most severely ischaemic group had the most dramatic increase of tissue perfusion after PTA. As such, PTA can be an effective method for increasing tissue perfusion even in the severely ischaemic diabetic feet.